The Role of Digital ESG Practices in Shaping Brand Perception and Consumer Engagement in the Beauty Industry - Shakila Kousar; Jianguo Du; Muhammad Umair Wattoo (SAGE Open)
The purpose of this study is to examine digital environmental, social, and governance (Digital ESG) practices in fundamentally changing brand perception elements, including brand image (BI), brand trust (BT), brand love (BL), brand attitude (BA), and their influence on social media engagement intention in the beauty industry which leads toward the overall engagement behavior of consumers in an online platform. A conceptual model was proposed, and data collected from 385 female respondents were analyzed using Structural Equation Modeling (SEM) to examine the relationships between Digital ESG practices, brand perception elements, social media engagement intentions, and engagement behaviors, including consumption, contribution, and content creation. The study’s findings demonstrate that Digital ESG practices have a positive influence on brand elements, leading to increased social media engagement intentions among potential consumers. This engagement translates into behavior, leading consumers to adopt environmentally friendly beauty products and reinforcing the importance of sustainability-driven brand strategies in digital marketplaces. This study contributes to the existing literature by bridging the gap between Digital ESG practices and consumer engagement in the beauty industry, particularly in an emerging market context. The findings offer practical implications for beauty brands seeking to enhance long-term consumer relationships, strengthen brand loyalty, and drive sustainable product adoption through responsible digital strategies.